2021
DOI: 10.1017/s1537592721001985
|View full text |Cite
|
Sign up to set email alerts
|

New Directions in Rebel Governance Research

Abstract: Day to day governance of civilians is not solely the purview of states. Rulemaking, rule-enforcing, and goods and services provision are central components of governance, yet in many instances it is non-state actors who assume these functions. We advance the study of governance by rebel groups engaged in armed confrontation against state governments. We identify five key areas of research where the field of rebel governance is best poised to go: the study of multi-level governance, rebel use of self-constraini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 83 publications
0
12
0
3
Order By: Relevance
“…In addition to insights into how groups adapt to shocks such as pandemics, this article also contributes to a growing body of research challenging the assumption that territorial control is a prerequisite for governance (e.g. Florea, 2018;Loyle et al, 2023;Waterman, 2023;Newman, Saikia, and Waterman 2023). We show that in areas of Colombia contested by multiple armed groups, both criminal and political groups are engaging in a wide variety of governance activities -including establishing rules to regulate civilian behaviour, demanding the payment of taxes, and providing services including economic benefits and dispute resolution to civilians in their territories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to insights into how groups adapt to shocks such as pandemics, this article also contributes to a growing body of research challenging the assumption that territorial control is a prerequisite for governance (e.g. Florea, 2018;Loyle et al, 2023;Waterman, 2023;Newman, Saikia, and Waterman 2023). We show that in areas of Colombia contested by multiple armed groups, both criminal and political groups are engaging in a wide variety of governance activities -including establishing rules to regulate civilian behaviour, demanding the payment of taxes, and providing services including economic benefits and dispute resolution to civilians in their territories.…”
Section: Discussionmentioning
confidence: 99%
“…This article also contributes to broader debates about the conditions under which armed groups govern (Arjona, 2016;Arias and Barnes, 2017;Barnes, 2017;Florea, 2018;Stewart, 2018;Lessing, 2021;Loyle et al, 2023;Waterman, 2023). Research on armed group governance has tended to focus on areas of monopolistic control (e.g.…”
mentioning
confidence: 96%
“…Nelson-Nuñez (2019), for instance, uses evidence from Peru to demonstrate that NGOs can either strengthen or weaken relationships between individuals and the government, based on whether the NGOs appear to be replacing the need for government interaction or not, and how much information the NGO provides. Work on rebel groups by Loyle et al (2022) and Loyle et al (2023) questions whether our focus on the state as the default provider may be misguided. In the context of firms specifically, Dawkins (2021) finds that government contracting-companies delivering a service that is funded by governments-can reduce citizen buy-in, creating a situation where people blame governments for failures and do not believe the government to be accountable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we contribute to a growing literature on rebel governance by considering the effects on development in areas that have experienced control by insurgents. Scholars have recently shown that non-state actors can govern the political, economic, and social lives of residents in an orderly fashion and establish institutions that regulate civilian behaviors (Arjona, 2016;Breslawski, 2021;Loyle et al, 2021;Stewart, 2018;Sánchez De La Sierra, 2020;Grasse, Sexton and Wright, 2021).…”
Section: Introductionmentioning
confidence: 99%